APLIKASI BOKASHI KOTORAN WALET DAN PUPUK TSP TERHADAP PERTUMBUHAN SERTA PRODUKSI TANAMAN KACANG PANJANG RENEK (Vigna unguiculata var. sesquapedalis) - Dela Andreya; Fathurrahman (DINAMIKA PERTANIAN, 2025)
This study aimed to determine the interaction and main effects of bokashi swallow droppings and TSP fertilizer on the growth and production of short long bean plants. The research was conducted at the Experimental Farm of the Faculty of Agriculture, Universitas Islam Riau, located at Jalan Kharuddin Nasution, Km 11, No. 113, Air Dingin Village, Bukit Raya District, Pekanbaru City. It was carried out for four months, from August to November 2022. The design used in this study was a Completely Randomized Factorial Design with two factors. The first factor was the application of bokashi swallow droppings, with four levels: 0, 250 g, 500 g, and 750 g per plot. The second factor was TSP fertilizer, with four levels: 0, 12.5 g, 25 g, and 37.5 g per plot. Parameters observed were plant height, flowering age, harvesting age, the longest pod length, pod weight per plant, pod weight per pod, number of pods per plant, number of remaining pods, root volume, and weight of 100 dry seeds. Observational data were analyzed statistically, and the Honest Significant Difference Follow-up Test was performed at the 5% significance level. The results showed that the interaction between bokashi swallow droppings and TSP fertilizer had a significant effect on plant height, the longest pod length, pod weight per plant, pod weight per pod, number of pods per plant, number of remaining pods, and root volume. The main effect of swallow droppings bokashi was significant on all parameters, with the optimal dose being 500 g per plot. The main effect of TSP fertilizer was significant on all parameters, with the optimal dose being 37.5 g per plot.